BIPOC alliances : building communities and curricula - Bailey, Indira; García, Christen Sperry; Reed, Glynnis; Sotomayor, Leslie C., II (Curriculum and pedagogy series., 2022)
"BIPOC Alliances: Building Communities and Curricula is a collection of reflective experiences that confront, challenge, and resist hegemonic academic canons. BIPOC perspectives are often scarce in scholarly academic venues and curriculum. This edited book is a curated collection of interdisciplinary, underrepresented voices, and lived experiences through critical methodologies for empowerment (Reilly & Lippard, 2018). Gloria Anzaldúa's (2015) autohistoria-teoría is a lens for decolonizing and theorizing of one's own experiences, historical contexts, knowledge, and performances through creative acts, curriculum, and writing. Gloria Anzaldúa coined, autohistoria-teoría, a feminist writing practice of testimonio as a way to create self-knowledge, belonging, and to bridge collaborative spaces through self-empowerment. Anzaldúa encouraged us to focus towards social change through our testimonios and art, "[t]he healing images and narratives we imagine will eventually materialize" (Anzaldúa & Keating, 2009, p. 247). For this collection, we use lived experience or testimonios as an approach, a method, to conduct research and to bear witness to learners and one's own experiences (Reyes & Rodríguez, 2012). Maxine Greene's (1995) concept of an emancipated pedagogy merges art, culture, and history as one education that empowers students with Gloria Anzaldúa's (2015) autohistoria-teoría to re-imagine individual and collective inclusion by allowing students "... to read and to name, to write and to rewrite their own lived worlds" (Greene, 1995, pp. 147). Greene and Anzaldúa reach beyond theorizing and creating curriculum for awareness and expand the crossings into active and critical self-reflective work to rewrite one's own empowered stories and engage in a healing process"--